(untitled) (Anclajes, 2021)
A panorama of the advances on the 19th century produced in the criticism of the last decades is displayed from the initial imprint of Ángel Rama’s legacy to the so-called material turn. The relevance that research on the periodical format acquired in studies on literary production, circulation and reception in that century is described and the contributions published in Anclajes are reviewed as a correlate of broader perspectives on publishing, literature, and reading.